ATIVIDADES DE EXTENSÃO PARA ENTIDADES SEM FINS LUCRATIVOS E PARA EMPREENDIMENTOS DA ECONOMIA SOLIDÁRIA - Rauber, Caroline; Didone, Marcelo L.; Basso, Lauri; Amaral, Simone L. d. (Salão do Conhecimento, 2013)
Resumo